Identification of a virus causing leaf distortion disease of papaya in Andhra Pradesh as cucumber mosaic cucumovirus - and P. SREENIVASULU*, G. KIRANMAI, M. HEMA (Indian Phytopathology, 2002)
A virus disease with mosaic, leaf distortion and filiform symptoms on commercially growing papaya (Carica papaya L.) around Kovvur, West Godavari district, Andhra Pradesh state was noticed during 1995. The sap transmissible virus from papaya leaves was successfully purified and its yield ranged from 7-9 mg/l00g leaf tissue. Its A 26M80 and Amn/minratio was 1.70 and 1.25, respectively. The purified virus was infectious to papaya. In DAC-ELlSA, the virus positively reacted with three cucumber mosaic cucumovirus (CMV) antisera but not with tobacco etch potyvirus, datura leaf distortion potyvirus and tobacco mosaic tobamovirus antisera. The coat protein of purified virions in SDS-PAGE was resolved into one major polypeptide with Mr of 26.2 kDa. The isolated genomic nucleic acid from purified VifUS in agarose gel was resolved into three genomic and one sub-genomic RNAs with Mr of 1.23, 1.12, 0.77 and 0.3 x 10 6 daltons, respectively. The double stranded (ds) RNA isolated from infected papaya leaves was resolved in agarose gel into three species with Mr of 2.46, 2.24 and 1.54xl06 daltons. Based on antigenic, coat protein and nucleic acid properties, the virus causing leaf distortion disease of papaya was identified as an isolate of CMV antigenically identical to CMV-Banana and CMV-Chilli isolates previously reported from Andhra Pradesh. This is probably the first report on natural infection of papaya with CMV in India.